STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING DI SMP NEGERI 4 METRO - Wahyu123# Fathur; Iswati; heri cahyono; Bayu Ardiwansyah (PROFETIK: Jurnal Mahasiswa Pendidikan Agama Islam, 2026)
This study aims to describe the strategies of Islamic Religious Education teachers in implementing the Problem Based Learning (PBL) model, students' critical thinking skills, as well as supporting and inhibiting factors in the implementation of PBL at SMP Negeri 4 Metro. This study uses a qualitative approach with a descriptive research type. Research informants include Islamic Religious Education teachers, the Deputy Head of Curriculum, and students who were selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. The results show that teacher strategies in implementing PBL are carried out through the planning, implementation, and evaluation stages of learning by utilizing discussion, question and answer, presentation, assignment, and practice methods. Students' critical thinking skills show varying developments in the aspects of understanding problems, analyzing information, expressing opinions, and drawing conclusions, although they still require habituation and guidance. Supporting factors for the implementation of PBL include teacher competence, student cooperation, and school support, while inhibiting factors include differences in student abilities, limited learning time, and less conducive classroom conditions. The implementation of PBL provides opportunities for students to be more active in the learning process and problem solving in Islamic Religious Education subjects.